PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT PT.PERKEBUNAN NUSANTARA VII BAGIAN KANTOR KOMODITI TEH 2 - Ricky Yoseptry; Silmi Aghnia Khaerunnisa; Aditya Nur Prayoga (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Information systems are connected components that work together to collect, process, store and disseminate information to support decision making, coordination, control and to provide an overview of activities within the company, especially in archiving mail data. Archives are documentation of activities or events packaged in various forms made and received by institutions. In a company, data archives are one of the important points that are very influential. PT Perkebunan Nusantara VIII, especially the Tea Commodity Office 2 which is in charge of controlling plantations in West Java, should have a modern and structured letter data archiving information system, but in fact the data is not organized and can even be accessed by anyone. A letter archive information system application is needed so that it can help overcome obstacles in managing documents properly and limiting access rights. The application design is made object oriented using UML (Unified Modeling Language) using the Waterfall method because this method can develop software that allows system development to be carried out in a structured and systematic manner.